PENGARUH PENAMBAHAN SERAT KAWAT BENDRAT TERHADAP KUAT TEKAN DAN KUAT TARIK BETON NORMAL - A, Arman; Sanjaya, Faldi; Wardi, Syafri (Jurnal Teknologi dan Vokasi, 2023)
Along with the progress of the times, technology in the field of building construction has also experienced rapid development, including concrete technology, almost every aspect of human life is always related to concrete. The use of added materials has been widely used in the concrete mix process. Based on this, this study aims to determine the increase in the compressive strength and optimal split tensile strength of concrete with added material of bendrat wire fiber, and the percentage addition of 0%, 4%, 5%, 6%, the tensile strength of concrete is only around 9% - 15 % of compressive strength. The approximation value obtained from repeated testing reaches a strength of 0.50 – 0.60ƒ????′, so for zero-mal concrete a value of 0.57ƒ????′ can be used. The analysis review of this research is the compressive strength and split tensile strength, with a concrete cylinder test object with a diameter of 15 cm and a height of 30 cm. The results obtained from normal concrete with a compressive strength of 9,62 N/mm2, and a compressive strength of 4%, with a result of 13,01 N/mm2, and a compressive strength of 5%, with a result of 12,45 N/mm2, and a compressive strength of 6 %, with a yield of 11,03 N/mm2. The quality of the concrete planned for K 225 which was tested at the age of 3 and 28 days was 48 samples and consisted of 3 variations, each variation of 6 samples. From the research, it was found that the highest compressive strength of concrete at the age of 3 days was 12,45 Mpa with, at the age of 28 days the highest compressive strength of concrete was 22,08 Mpa. The lowest compressive strength value of concrete at the age of 3 days is 9,62 Mpa with the lowest value of concrete compressive strength at the age of 28 days is 14,72 Mpa. It can be concluded in this study that the more wire fibers used, the higher the value of the compressive strength of concrete. From the research, it was found that the highest split tensile strength of concrete at the age of 3 days was 13,01 Mpa with, at the age of 28 days the highest value of the split tensile strength of concrete was 22,08 Mpa. The value of the lowest split tensile strength of concrete at the age of 3 days is 9,62 Mpa with the lowest value of split tensile strength of concrete at the age of 28 days is 14,72 Mpa. It can be concluded in this study that the more wire fibers used, the higher the value of the compressive strength of concrete.